Mapping of Cervical and Upper Mediastinal Lymph Node Recurrence for Guiding Clinical Target Delineation of Postoperative Radiotherapy in Thoracic Esophageal Squamous Cell Carcinoma - Wang, Yichun; Ye, Dongmei; Kang, Mei; Zhu, Liyang; Yang, Mingwei; Jiang, Jun; Xia, Wanli; Kang, Ningning; Chen, Xiangcun; Wang, Jie; Wang, Fan (Frontiers in Oncology, 2021)
Background: The lower neck and upper mediastinum are the major regions for postoperative radiotherapy (PORT) in thoracic esophageal squamous cell carcinoma (TESCC). However, there is no uniform standard regarding the delineation of nodal clinical target volume (CTVnd). This study aimed to map the recurrent lymph nodes in the cervical and upper mediastinal regions and explore a reasonable CTVnd for PORT in TESCC. Methods: We retrospectively reviewed patients in our hospital with first cervical and/or upper mediastinal lymph node recurrence (LNR) after upfront esophagectomy. All of these recurrent lymph nodes were plotted on template computed tomography (CT) images with reference to surrounding structures. The recurrence frequency at different stations was investigated and the anatomic distribution of recurrent lymph nodes was analyzed. Results: A total of 119 patients with 215 recurrent lymph nodes were identified. There were 47 (39.5%) patients with cervical LNR and 102 (85.7%) patients with upper mediastinal LNR. The high-risk regions were station 101L/R, station 104L/R, station 106recL/R, station 105 and station 106pre for upper TESCC and station 104L/R, station 106recR/L, station 105, station 106pre and station 106tbL for middle and lower TESCCs. LNR in the external group of station 104L/R was not common, and LNR was not found in the narrow spaces where the trachea was in close contact with the innominate artery, aortic arch and mediastinal pleura. LNR below the level of the cephalic margin of the superior vena cava was also not common for upper TESCC. Conclusions: The CTVnd of PORT in the cervical and upper mediastinal regions should cover station 101L/R, station 104L/R, station 106recL/R, station 105 and station 106pre for upper TESCC and station 104L/R, station 106recL/R, station 105, station 106pre and station 106tbL for middle and lower TESCCs. Based on our results, we proposed a useful atlas for guiding the delineation of CTVnd in TESCC.